Over-the-top sport: live streaming services, changing coverage rights markets and the growth of media sport portals. (October 2019) - Hutchins, Brett; Li, Bo; Rowe, David
The growth of over-the-top (OTT) Internet and mobile video streaming services is a major development in the distribution, transmission and consumption of global media sport. Heavily capitalised services such as Tencent Video, DAZN and Amazon Prime Video are intervening in coverage rights markets and changing how live sport is experienced and shared across television, computer, game console, tablet and smartphone screens. This article identifies and analyses six defining characteristics of OTT live sport streaming, and outlines three services (Tencent Video, DAZN and Amazon Prime Video) that operate across Asia, the United Kingdom, Europe, the Americas and Australasia. Its argument is that, first, live sport streaming is a key means by which television content and practices are escaping the boundaries of broadcast media, while also continuing to perpetuate the logics of television coverage and viewing practices. Second, drawing on Amanda D. Lotz's conceptualisation of portals, it is proposed that these services are establishing new norms concerning how media sport is accessed and curated and, as such, their arrival signals a historic shift in the global marketplace for sport coverage rights and the media systems through which live content circulates.